Alcohol e‐Help: study protocol for a web‐based self‐help program to reduce alcohol use in adults with drinking patterns considered harmful, hazardous or suggestive of dependence in middle‐income countries. (26th October 2017) - Schaub, Michael P.; Tiburcio, Marcela; Martinez, Nora; Ambekar, Atul; Balhara, Yatan Pal Singh; Wenger, Andreas; Monezi Andrade, André Luiz; Padruchny, Dzianis; Osipchik, Sergey; Gehring, Elise; Poznyak, Vladimir; Rekve, Dag; et al.
Abstract: Background and aims: Given the scarcity of alcohol prevention and alcohol use disorder treatments in many low and middle‐income countries, the World Health Organization launched an e‐health portal on alcohol and health that includes a Web‐based self‐help program. This paper presents the protocol for a multicentre randomized controlled trial (RCT) to test the efficacy of the internet‐based self‐help intervention to reduce alcohol use. Design: Two‐arm randomized controlled trial (RCT) with follow‐up 6 months after randomization. Setting: Community samples in middle‐income countries. Participants: People aged 18+, with Alcohol Use Disorders Identification Test (AUDIT) scores of 8+ indicating hazardous alcohol consumption. Intervention and comparator: Offer of an internet‐based self‐help intervention, 'Alcohol e‐Health', compared with a 'waiting list' control group. The intervention, adapted from a previous program with evidence of effectiveness in a high‐income country, consists of modules to reduce or entirely stop drinking. Measurements: The primary outcome measure is change in the Alcohol Use Disorders Identification Test (AUDIT) score assessed at 6‐month follow‐up. Secondary outcomes include self‐reported the numbers of standard drinks and alcohol‐free days in a typical week during the past 6 months, and cessation of harmful or hazardous drinking (AUDIT < 8). Analysis: Data analysis will be by intention‐to‐treat, using analysis of covariance to test if program participants will experience a greater reduction in their AUDIT score than controls at follow‐up. Secondary outcomes will be analysed by (generalized) linear mixed models. Complier average causal effect and baseline observations carried forward will be used in sensitivity analyses. Comments: If the Alcohol e‐Health program is found to be effective, the potential public health impact of its expansion into countries with underdeveloped alcohol prevention and alcohol use disorder treatment systems world‐wide is considerable.